Unlocking Tax Compliance Intention MSMEs: Exploring the Roles of Tax Moral, Incentives, and Trust in Government - Fadhilatunisa, Della; Hajar Dewantara; Andika Isma; Masdar Ryketeng; Muhammad Nurfaizy Hamdan (PT Mattawang Mediatama Solution, 2025)
This study addresses the persistent challenge of low tax compliance among Micro, Small, and Medium Enterprises (MSMEs), a sector that plays a vital role in economic growth and state revenue generation. Despite their strategic significance, MSMEs often demonstrate inadequate compliance with tax regulations due to a range of psychological, institutional, and financial factors. The objective of this research is to examine the influence of tax moral, tax incentives, and trust in government on the tax compliance intentions of MSME actors. Employing a quantitative research approach with a cross-sectional survey design, the study targeted MSME owners and managers in Makassar as its population. Respondents were selected through stratified random sampling to ensure representation across different business sizes and sectors. Data were collected using a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that tax moral, tax incentives, and trust in government each have a significant positive effect on MSMEs’ tax compliance intentions, with tax moral emerging as the most influential factor. These results highlight the necessity for integrated policies that strengthen ethical tax awareness, optimize incentive programs, and improve public trust in government institutions. The study’s implications suggest that such multidimensional strategies are essential for enhancing voluntary tax compliance. However, the research is limited by its focus on a specific regional context and cross-sectional design, indicating the need for broader and longitudinal investigations in future studies.